Impact of strengthening exercises with and without Blood Flow Restriction on Quadriceps of Knee Osteoarthritis patients. - Rida Shakeel; Atif Ahmad Khan; Aisha Ayyub; Zahra Masood (Journal of the Pakistan Medical Association, 2021)
Aims and Objectives: To determine the effect of Blood Flow Restriction with strengthening exercises on Knee Osteoarthritis patients. Subjects and Method: This case-control study was conducted at Department of Physical Medicine and Rehabilitation in Combined Military Hospital Okara after signing ethical approval letter by ethical committee from June 2018 to December 2018 with 30 Knee Osteoarthritis participants selected by non-purposive consecutive sampling among which 15 participants were assigned to group A (strengthening exercises with blood flow restriction) and 15 to group B (strengthening exercises without blood flow restriction) using lottery method. 16 sessions were arranged for both groups with 4 sessions per week for 4 weeks with 5 minutes warm up on a stationary bike. Visual Analogue Scale and Kujala Scoring Questionnaire were applied for outcome measures. Results were analyzed by paired-t test and independent-t test using Statistical Package for Social Sciences 20. Result: Most of participants were female i.e. 66.7% with 70% had BMI value > 25 kg/m2. Significant improvement in pain on Visual Analogue Scale (p-value 0.00 for group A and 0.01 for group B) and disability on Kujala Scoring Questionnaire (p-value 0.00 for both groups) was found, but for Muscle Girth, group A showed significant improvement with p-value 0.01 as compared to group B with p-value 0.33. However, inter-group analysis showed no significant difference between outcome measures. Conclusion: Strengthening exercises reduce pain and disability. However, addition of blood flow restriction also improves muscle size and strength. Keywords: Knee Osteoarthritis, Strengthening Programs, Vascular Occlusion, Tourniquet, Continuous...